A CRITICAL ANALYSIS OF THE EU’S WMD STRATEGY:: A CASE STUDY OF IRAN (Journal of European Studies (JES), 2016)
This paper is an attempt to assess the significance of the first ever EU strategy to stop the proliferation of WMD by first taking a broad overview of the background which has led to its adoption and institutionalization. Secondly, the paper also attempts to address pertinent question whether the strategy is actually effective, and which issues are undermining the implementation of the strategy. Thirdly, Iran has been taken as a case study to evaluate the role of the EU in the crisis situation that emerged after the revelations regarding Iran’s development of nuclear weapons. In the last part, the paper gives conclusions on whether the EU’s strategy has achieved the desired goals in the matter of proliferation of WMD or it merely remains a declaratory policy even after more than a decade since its adoption.